Análisis de los Esquemas de Acceso Inalámbricos Propuestos para la Tercera Generación de Sistemas Celulares - Penagos, Hernán Paz (Ingeniería, 2001)
The current wireless communications have a bottle neck because their low speed (9600 bps); this prevents that new services shall be implemented linked over Internet and the transmission of data and images or he/she makes that they appear with limitations, like it happens with the services WAP (WIRELESS APPLICATION PROTOCOL). The net of current telecommunications evolves toward the attainment of an unified net (wire net and wireless net); the evolution of the net contemplates the evolution of the elements that you/they configure it; consequently, the access part will have to evolve to make possible more and better communications among ends, without preventing that the other ones make the own thing. The outlines of wireless access of wide band proposed for cellular communications of third generation look for to respond to the challenge. Of them, W-CDMA and CDMA2000 are imposed as the technologies of access of more efficiency.